Environment-Friendly Bromination of Aromatic Heterocycles Using a Bromide–Bromate Couple in an Aqueous Medium - Joshi, Girdhar; Adimurthy, Subbarayappa (Industrial & engineering chemistry research, 2011)
Selective monobromination of aromatic heterocyclic compounds through in-situ acid activation of 2:1 bromide/bromate couple as a benign brominating reagent is described. The in-situ acid activation of a bromide–bromate couple generates the reactive species BrOH, and it is proved to be an efficient for the bromination of various heterocycles under mild aqueous conditions without the use of any catalyst. Heterocycles that had electron-rich substituents provided good yields.